Does issue framing shape support for COVID-19 lockdown measures? Evidence from a survey experiment in Peru - Miguel Carreras; Sofia Vera; Giancarlo Visconti (Research & Politics)
Two issue frames quickly emerged in policy and media communications about COVID-19 lockdown measures. Initially, a public health frame advocated for strong quarantine policies to slow the spread of the virus. As the economic costs associated with quarantine measures became clear, an economic frame pushed for an end to (or a relaxation of) these measures to alleviate the economic damage associated with lockdowns. We do not know much about how these competing communication frames affected lockdown support, especially in poor- and middle-income countries. To explore this question, we embedded a framing experiment in a nationally representative telephone survey in May 2020 in Peru, one of the world’s hardest-hit countries by the coronavirus pandemic. The vignette experiment reveals that the economic frame produces a decrease in public support for quarantine measures in Peru. In contrast, respondents exposed to a health frame do not increase their approval of the same measures.